2019
DOI: 10.1016/j.celrep.2019.03.075
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone Increases Bifidobacterium Relative Abundance during Late Pregnancy

Abstract: Highlights d Bifidobacterium abundance increases in the gut during pregnancy in women and mice d Progesterone supplementation alters gut microbial composition in mice and in vitro d Progesterone supplementation increases Bifidobacterium abundance in mice and in vitro d We suggest that progesterone promotes Bifidobacterium growth during late pregnancy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
128
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 154 publications
(137 citation statements)
references
References 36 publications
5
128
1
3
Order By: Relevance
“…However, we are not the only group who found differences in gut microbiota during pregnancy. Also previous studies in mice have shown an effect of pregnancy on the abundance of gut microbiota species (14,36,37). However, each of these mouse studies found their own specific adaptations of the microbiota to pregnancy.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, we are not the only group who found differences in gut microbiota during pregnancy. Also previous studies in mice have shown an effect of pregnancy on the abundance of gut microbiota species (14,36,37). However, each of these mouse studies found their own specific adaptations of the microbiota to pregnancy.…”
Section: Discussionmentioning
confidence: 97%
“…The mechanism changing the microbiota during pregnancy are unclear at this time. However, it has been suggested that pregnancy hormones, like progesterone, may affect the gut microbiota (36). Also, diet has been shown to affect the gut microbiota (37).…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial 16S rRNA gene sequences from each sample were amplified by PCR performed in 96-well plates. Sample preparation was similar to that described by Nuriel-Ohayon et al [ 25 ]. Briefly, PCR reactions contained 17 μL PCR grade nuclease-free water (Hylabs, Rehovot, Israel), 25 μL PrimeSTAR Max (Takara-Clontech, Shiga, Japan), 2 μL each of the forward and reverse primers (10 μM final concentration), and 4 μL genomic DNA.…”
Section: Methodsmentioning
confidence: 99%
“…Reactions were heated to 95 °C for 3 min for DNA denaturation, with amplification proceeding for 33 cycles at 98 °C for 10 min, 55 °C for 5 min, and 72 °C for 5 min; a final extension of 1 min at 72 °C was added to ensure complete amplification. Barcoded universal primers 515F and 806R containing Illumina adapter sequences which target the highly conserved V4 region, as previously described [ 25 ], were used to amplify the microbiota from individual samples. Amplicons were purified using AMPure XP magnetic beads (Beckman Coulter, Brea, CA) and subsequently quantified using Quant-it Picogreen dsDNA quantification kit (Invitrogen, Carlsbad, CA).…”
Section: Methodsmentioning
confidence: 99%
“…Bifidobacterium is a genus that influences intestinal function in infants who have received healthy breast milk, while low but relatively stable Bifidobacterium counts are observed in adulthood [39]. The abundance of Bifidobacterium increases in the late stages of pregnancy in both women and mice, indicating the causative role of progesterone [40]. Bifidobacterium bifidum colonization increases interleukin 6 (IL-6) and IL-8 cytokine levels through NF-κB activation in mice [41].…”
Section: Discussionmentioning
confidence: 99%